Bulletin for industrial statistics for the Arab countries 2001-2007 (United Nations, 2010)
"... aims to provide detailed industrial data on Arab countries for the users of such statistics, including policymakers, analysts and researchers, in order to assist them in meeting their needs in this area. The publication includes time series of data and indicators for the period 2001-2007. Data are drawn from national sources, as well as from secondary sources where appropriate. The Bulletin is divided into two parts. Part I includes summary tables on overall industrial trends, including output levels,labour productivity, the contribution made by industry to the gross domestic product and average wages of employees. Part II contains tables of industrial statistics, where available, for each Arab country, including data on the number of establishments, the number of employees, wages and salaries, output, value added and industrial production index numbers."--Back cover.